Medical databases in the University of Malaya Library: Popline, Healthplan, CCIS, Immunology & AIDS - Sinnasamy, J. (University of Malaya Library, 1995)
It is generally known that doctors use the MEDLINE database mostfortheirliterature search. However, they must know that there are other medical databases available such as the PSYCLlT, CANCERLlT, AIRDSLlNE, etc. Some of these have yet to gain popularity and recognition among the medical personnel. Similarly the allied health personnel, such as the nurses, also tend to use only the Cumulative Index to Nursing and Allied Health Literature (CINAHL). Databases such as HEALTHPLAN, POPLINE are useful reference tools for them as the subject emphasis is more on the non-clinical aspects.